Workshops of the Pedagogic Week 2021 of Centro Universitario FMABC - Baldassin, Sergio; Feder, David; Oliveira, Silvia; Ortiz, Ana Carolina Mota; Nicolau, Ana Júlia Fernandes Abdala; Nardi, Gabriela de; Silva, Júlia; Faro Junior, Mario Paulo (ABCS Health Sciences, 2023)
Introduction: Delivering quality medical education is a hot topic. The current discussion essentially addresses content versus competencies. Extensive curricula and matrices, and traditional assessments are against go against the modern concepts of medical education. Remote education stimulated this discussion and brought the opportunity to review the academic load and assessment. Report: In January 2021, a pedagogic workshop of the Medicine course of Centro Universitário FMABC was held. It began with a lecture by a visiting professor and coordinator of the medical school accreditation system on remote activities during the pandemic. Next, the person responsible for the Progress Test made a history of the latest assessments, and a professor who is a member of the Accreditation Committee of the Medical Schools presented a summary of the main insufficient points of the last assessment. Afterward, the students presented the last internal evaluations. Finally, the matrices of the course, from the 1st to the 4th year, were presented and compared with those of three other medical schools, and each year coordinator prepared their suggestions for changes to the matrices. Lastly, professors and the course coordination presented a report and proposals, encouraging the integration of the academic community, the reassessment of teaching plans, repetition of content and recognition of matrices of each year, offering ideas and tools, to reflection on remote learning, and opportunities for change and improvement in teaching, and learning. Conclusion: The disciplines showed willingness for integrative activities, extension and creation of elective disciplines, complementing failures caused by the Pandemic.